Protocol to develop a core outcome set in incisional hernia surgery: the HarMoNY Project. Issue 12 (6th December 2022) - Harji, Deena; Thomas, Christophe; Antoniou, Stavros; Chandraratan, Harsha; Griffiths, Ben; Heniford, B Todd; Horgan, Liam; Koeckerling, Ferdinand; Lopez-Cano, Manuel; Massey, Lisa; Miserez, Marc; Montgomery, Agneta; et al.
Abstract : Introduction: Incisional hernia has an incidence of up to 20% following laparotomy and is associated with significant morbidity and impairment of quality of life. A variety of surgical strategies including techniques and mesh types are available to manage patients with incisional hernia. Previous works have reported significant heterogeneity in outcome reporting for abdominal wall herniae, including ventral and inguinal hernia. This is coupled with under-reporting of important clinical and patient-reported outcomes. The lack of standardisation in outcome reporting contributes to reporting bias, hinders evidence synthesis and adequate data comparison between studies. This project aims to develop a core outcome set (COS) of clinically important, patient-oriented outcomes to be used to guide reporting of future research in incisional hernia. Methods: This project has been designed as an international, multicentre, mixed-methods project. Phase I will be a systematic review of current literature to examine the current clinical and patient-reported outcomes for incisional hernia and abdominal wall reconstruction. Phase II will identify the outcomes of importance to all key stakeholders through in depth qualitative interviews. Phase III will achieve consensus on outcomes of most importance and for inclusion into a COS through a Delphi process. Phase IV will achieve consensus on the outcomes that should be included in a final COS. Ethics and dissemination: The adoption of this COS into clinical and academic practice will be endorsed by the American, British and European Hernia Societies. Its utilisation in future clinical research will enable appropriate data synthesis and comparison and will enable better clinical interpretation and application of the current evidence base. This study has been registered with the Core Outcome Measures in Effectiveness Trials initiative. PROSPERO registration number: CRD42018090084.